Organisational Factors Influencing E-business Adoption in Zimbabwe's Manufacturing Sector - S. Mupemhi; A. Muposhi (Journal of Economics and Behavioral Studies, 2018)
Creating and sustaining competitive advantage through the adoption and implementation of innovative technologies is a strategic imperative for all learning organizations. Despite this, manufacturing companies in developing countries such as Zimbabwe are confronting challenges in implementing e-business practices. Against this background, the objective of this study was to understand organizational factors influencing e-business adoption in Zimbabwe’s manufacturing sector. The study was motivated by the need to appreciate factors that facilitate or inhibit the adoption of e-business in the context of developing countries such as Zimbabwe. A questionnaire was distributed to a random sample of 118 companies registered by the Confederation of Zimbabwe Industries in 2015. Regression analysis was used to test the posited hypotheses. Results revealed that manufacturing companies in Zimbabwe differ significantly in their inclination to adopt and implement e-business strategies. Innovation orientation, financial resources, perceived usefulness and size of the firm were found to be positively associated with e-business adoption. The study also found that technological resources did not have a statistically significant relationship with e-business adoption. The study furthers current debate on e-business adoption by identifying the drivers of e-business adoption in the manufacturing sector in the context of a developing country. The importance of this study lies in its contribution to theory and practice. In terms of theory, this study contributes to the body of knowledge on organizational factors influencing e-business adoption and provides avenues for further studies. In practice, the findings of this study add to the insights of managers in the manufacturing sector in developing countries, which influence the adoption of e-business practices.